2014
DOI: 10.1186/preaccept-2264226161402830
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative assessment of Azumiobodo hoyamushi distribution in the tunic of soft tunic syndrome¿affected ascidian Halocynthia roretzi using real-time polymerase chain reaction

Abstract: Background: The kinetoplastid parasite, Azumiobodo hoyamushi, is the causative agent of soft tunic syndrome (STS) in ascidians and leads to their mass mortality in Korean waters. This study was conducted to quantify A. hoyamushi density during the development of STS in the tunics of ascidians (Halocynthia roretzi) using real-time polymerase chain reaction (qPCR). Findings: The infection intensity of A. hoyamushi, as measured by qPCR, varied depending on the part of the tunic analyzed, as well as the stage of S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…In particular, the inhalent tissue of ascidians was removed and used for quantification of the pathogen. Shin et al [ 11 ] examined the infection intensity of A. hoyamushi in various parts of the tunic, including inhalent siphon, exhalent siphon, and three different parts of the tunic; they found that the inhalent siphon was the most sensitive organ for the diagnosis of the pathogen. They also reported that infection intensity of A. hoyamushi increased as STS developed and the pathogens spread to other parts of the tunic from the inhalent siphon.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In particular, the inhalent tissue of ascidians was removed and used for quantification of the pathogen. Shin et al [ 11 ] examined the infection intensity of A. hoyamushi in various parts of the tunic, including inhalent siphon, exhalent siphon, and three different parts of the tunic; they found that the inhalent siphon was the most sensitive organ for the diagnosis of the pathogen. They also reported that infection intensity of A. hoyamushi increased as STS developed and the pathogens spread to other parts of the tunic from the inhalent siphon.…”
Section: Discussionmentioning
confidence: 99%
“…After pulverization of 150 mg of each sample, DNA was extracted using DNA blood kit (Qiagen) and A. hoyamushi was quantified using the Taq-Man probe technique [ 11 ]. The primer used in the qPCR was F: 5′-GCC TCT GTG GTT TGC TCC TT-3′, R: 5′-TAC TGG GCG GCT TGG ATC TCG T-3′ and the probe was 5′ FAM-CCG CTC AAA GAC GAA CTA CAG CGA -BHQ1 3′.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation